PRODUKTIFITAS PERAWAT BERDASARKAN STANDAR ASUHAN KEPERAWATAN - Asrie Abu (Jurnal Kesehatan Manarang, 2017)
The quality of nursing service influenced by productivity of nurses in implementing nursing care according to standard. The objective of this study is determine productivity of nurses based on nursing care standards at inpatient rooms of Lanto Dg Pasewang hospital on 2013. The sample in this study are nurses in inpatient room as many as 124 peoples obtained through exhaustive sampling method. The data collected by interview using questionnaire. Data were analyzed by univariate analysis. The variables are nursing productivity. The result of the research showed that most of respondents are 62,9% in 21-25 years old age group, 79,8% female gender, 75% educated as diploma, 67,7% unmarried, 46 % has 1-2 years of service, and 29,8% worked at Lontara 2. Based on univariat analysis showed that majority of nurses did not implementing nursing care according to standard (64,5%). It expected that the hospital management made strategic effort to increase the productivity of nurse according to nursing care standard.